2016
DOI: 10.1007/s00586-016-4777-9
|View full text |Cite|
|
Sign up to set email alerts
|

Biomechanical consideration of prosthesis selection in hybrid surgery for bi-level cervical disc degenerative diseases

Abstract: Each disc prosthesis has its biomechanical advantages and disadvantages in HS and should be selected on an individual patient basis. In general, ProDisc-C, Mobi-C, and Discover produced similar performances in terms of spinal motions, adjacent IDPs, and driving moments, whereas Bryan and PCM produced similar biomechanical performances. Therefore, HS with Discover, Bryan, and PCM may be suitable for patients with potential risk of facet joint degeneration, whereas HS with ProDisc-C, Mobi-C, and Discover may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…The element sizes for bone and skin were 2.5 and 1.5 mm, respectively, that resulted in a total of 94,522 nodes and 306,289 elements. Convergence within 3% in joint cartilage stress was achieved in bare feet weight-bearing condition, to ensure that the results were irrelevant to the mesh density [19, 20]. …”
Section: Methodsmentioning
confidence: 99%
“…The element sizes for bone and skin were 2.5 and 1.5 mm, respectively, that resulted in a total of 94,522 nodes and 306,289 elements. Convergence within 3% in joint cartilage stress was achieved in bare feet weight-bearing condition, to ensure that the results were irrelevant to the mesh density [19, 20]. …”
Section: Methodsmentioning
confidence: 99%
“…The finite element models evaluated the ROM in the levels adjacent to HS (Jia et al, 2014). Some studies compared the biomechanics with different hybrid construct in two-level cervical degenerative disc disease using different dynamic implants of various structure and material properties (Cho et al, 2010;Li et al, 2017;Mo et al, 2017). Cervical fusion was shown to change the ROM distribution of the cervical segments and lead to hypermobility as well as increased burden at the adjacent levels (Natarajan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Cervical fusion was shown to change the ROM distribution of the cervical segments and lead to hypermobility as well as increased burden at the adjacent levels (Natarajan et al, 2000). HS is beneficial to motion preservation of the operated levels and produced a ROM of the entire operated and adjacent levels close to that of the healthy spine, resulting in less adverse effect on adjacent segments (Natarajan et al, 2000;Mo et al, 2017). Immobilization and segmental motion were achieved at the fusion level and arthroplasty level, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Proponent surgeons claim to also use it for biomechanical considerations in certain patients. Mo et al 30 reported on biomechanical considerations of multiple CDA devices selected in hybrid surgery for bilevel cervical degenerative disc disease using finite element analysis. The authors concluded that Prodisc-C, Mobi-C, and Discover performed similarly with respect to spinal motion, adjacent intradiscal pressures, and driving moments, while Bryan and PCM were more comparable biomechanically.…”
Section: Inclusion Criteriamentioning
confidence: 99%